1959
DOI: 10.1172/jci103802
|View full text |Cite
|
Sign up to set email alerts
|

On the Rate of Hydrocortisone Clearance From Plasma in Pregnant Women and in Patients With Laennec's Cirrhosis*

Abstract: The question of whether or not there is an increase in adrenal cortical secretion during pregnancy remains unsettled. Morphologic studies of the adrenal during gestation have revealed enlargement of the gland in some species (1) and no enlargement in others (2). In the human female, several groups of investigators have observed a progressive rise in the plasma 17-hydroxycorticosteroid (17-OH-corticosteroid) level during pregnancy (3-8). Paper chromatographic studies (9), confirmed in this laboratory (10), have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1960
1960
1983
1983

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 28 publications
(41 reference statements)
1
6
0
Order By: Relevance
“…These high values constitute (18). As will be seen (Section 3 below), the same distribution between plasma and CSF is found with cortisol-21-hemisuccinate as with free cortisol.…”
Section: Methodssupporting
confidence: 54%
See 1 more Smart Citation
“…These high values constitute (18). As will be seen (Section 3 below), the same distribution between plasma and CSF is found with cortisol-21-hemisuccinate as with free cortisol.…”
Section: Methodssupporting
confidence: 54%
“…As will be seen (Section 3 below), the same distribution between plasma and CSF is found with cortisol-21-hemisuccinate as with free cortisol. is considerably more rapid than that found in normal human subjects (27 per cent per hour) (18) or "half-time" of 138 minutes (19).…”
Section: Methodsmentioning
confidence: 59%
“…The rise in CBG concentration is thought to lead to a decrease in the met abolic clearance rate of cortisol in pregnancy [13]. It is interesting that Cohen et al [2] found a half-life for exogenously administered cortisol of 204 min in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…The last trimester of pregnancy is associated with similar changes in levels of plasma 17-OHCS and in their response to exogenous ACTH (3)(4)(5)(6)(7)(8)(9). In the last trimester of pregnancy there is a variable increase in urinary 17-OHCS excretion, a decrease in the rate of clearance of exogenous cortisol from plasma (9)(10)(11), a decrease in the rate of clearance of exogenous tetrahydrocortisone from plasma (11) and an increase in corticosteroid-binding protein (12). The apparently normal adrenal status of pregnant women and of patients treated with estrogens for long periods of time suggests that the administration of estrogens to man elevates plasma 17-OHCS levels by altering the normal metabolism of endogenous cortisol by a mechanism similar to that seen in pregnancy.…”
mentioning
confidence: 99%